Sustainability strategies in the beverage industry: a longitudinal study of Ambev in Brazil (2014-2024) - Andrade, Gabrielly de Souza; Oliveira, Rodrigo Ribeiro de; Gonçalves, Wellington; Oliveira, Mauro Machado de (Brazilian Journal of Production Engineering, 2025)
Sustainability has become an essential element for modern industry, especially in sectors with high resource consumption, such as the beverage industry. This article aims to analyze the actions and challenges of the sustainable strategies adopted by Companhia de Bebidas das Américas (Ambev) in Brazil between 2014 and 2024, in accordance with the United Nations Sustainable Development Goals (SDGs). This is a qualitative study with a longitudinal approach, based on document analysis of institutional reports, using content analysis techniques. The results show significant progress, such as reduced water consumption, use of renewable energy, increased use of recycled packaging materials, and the early achievement of environmental goals. However, limitations were also identified, including dependence on self-reported data and a lack of comparative information with other companies in the sector. The study also identified positive social impact initiatives, such as productive inclusion programs and access to drinking water. It is concluded that Ambev has integrated sustainability into its business model, although there are opportunities for improvement regarding transparency and results measurement, demonstrating that it is possible to combine economic competitiveness with environmental and social responsibility based on the principles of Production Engineering.